PENERAPAN SISTEM MANAJEMEN KINERJA DI PT. HAMDALAH MONEY CHANGER JEMBER (INDIKATOR: EVALUASI KINERJA HAMBATAN KINERJA DAN PENILAIAN KINERJA) - Kisma Kamila; Siti Washifa Jannati; Aprilya Fitriani (Jurnal Riset Multidisiplin Edukasi, 2026)
The purpose of this study is to determine the implementation of the performance management system through the evaluation process, Performance Barriers and performance assessment at PT. Hamdalah Money Changer Jember. The method used in this study uses a qualitative method with direct observation and interviews with the Directors of PT. Hamdalah Money Changer Jember. The results of the study indicate that (1) The Performance Management System at PT. Hamdalah Changer Jember is family-like, simple, informal, and focuses on SOP standards. (2) The Performance Evaluation Process of PT. Hamdalah Money Changer Jember is carried out through interpersonal communication. (3) Performance Barriers at PT. Hamdalah in implementing the performance management system lie in the absence of clear work target determination, and the family-like Work System also has the potential to cause a lack of discipline and professionalism because there are no clear boundaries between personal relationships and work responsibilities, and other obstacles are seen in the performance evaluation process which is still simple and carried out internally without involving structured assessment indicators, the next obstacle lies in the generalized payroll system. (4) Performance assessment of PT. Hamdalah is carried out based on the results of observations, experiences and considerations of management regarding employee behavior and work achievements while carrying out their duties.